La Gestión de Talento Humano por Competencia y la Calidad de Servicio que presta el personal del Centro de Turismo Comunitario Chalwa Organik. - Bone Rodríguez, Lissette Deyanire (2023)
The research project focuses on competency-based human talent management and service quality at Chalwa Organik Community Tourism Centre. Human talent management refers to an organization's ability to attract, integrate, develop, and retain highly qualified workers to meet current and future business objectives. On the other hand, competency management focuses on an integrated combination of knowledge, skills, and attitudes that lead to an appropriate and timely performance in various contexts. A questionnaire with 17 questions distributed in three study variables was used to state the project's objectives: competency-based human talent management, quality of service, and the Chalwa Organik Community Tourism Centre. The Cronbach's alpha found was excellent, with a value of 0.935, indicating a high internal consistency in the participants' responses. A hypothetical-deductive research method was used with a non-experimental, field- based research design, where a sample was not used because the population size was reductive. The research demonstrated a positive and significant correlation of 0.751 between competency- based human talent management and service quality at Chalwa Organik Community Tourism Centre. It indicates that good competency-based human talent management can positively impact the service quality of the tourism center. Despite the positive results, there were some areas where human talent management and service quality could be improved at Chalwa Organik Community Based Tourism Centre. In particular, it is recommended to improve the incentives offered to employees, provide training to improve their skills and knowledge, clarify the roles and responsibilities of employees, and improve the competitiveness of the tourism center in comparison to other tourism destinations in the area.